2009
DOI: 10.1016/j.matbio.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Site controlled transgenic mice validating increased expression from human matrix metalloproteinase (MMP-1) promoter due to a naturally occurring SNP

Abstract: Matrix Metalloproteinases (MMPs) comprise a family of more than 20 members, each with the ability to degrade components of the extracellular matrix. The interstitial collagenases have the unique capacity to degrade the stromal collagens, types I, II and III, the body's most abundant proteins. These collagenases include MMP-1, MMP-8, MMP-13 and MMP-14. MMP-1, with a very broad expression pattern, has major roles in mediating matrix destruction in many diseases. We have described a single nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(60 reference statements)
1
7
0
1
Order By: Relevance
“…This binding site is close to an AP‐1 site, promoting a 37‐fold increase in transcription activity, in vitro (12). A recent study of the same group, using transgenic mice, validated the increased expression of the MMP1 2G allele in vivo (27).…”
Section: Discussionmentioning
confidence: 93%
“…This binding site is close to an AP‐1 site, promoting a 37‐fold increase in transcription activity, in vitro (12). A recent study of the same group, using transgenic mice, validated the increased expression of the MMP1 2G allele in vivo (27).…”
Section: Discussionmentioning
confidence: 93%
“…The MMP1 rs1799750 and MMP12 rs2276109 variants investigated in this study are promoter polymorphisms and have been shown to have functional effects (Rutter et al, 1998; Jormsjo et al, 2000; Coon et al, 2009). The 2G allele of the MMP1 rs1799750 variant creates an Ets binding site (5′‐GGA‐3′) and it has been shown to have significantly higher transcription of the MMP1 gene, when compared with the 1G allele (Rutter et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The level of MMP1 expression is influenced by polymorphism in the promoter region of MMP1 (22). Such polymorphism affects both transcription of MMP1 and enzyme activity (23). Indeed, the -340A→G polymorphism (rs514921) of MMP1 affects the binding of transcription factors and influences the level of MMP1 expression (22,24).…”
Section: Discussionmentioning
confidence: 99%